Heritage resources and the development of tourist areas in the High Atlas and southern regions of Morocco - Saïd Boujrouf (Revue de Géographie Alpine)
Morocco is currently implementing a decentralization model based on the territorial project approach. Introduced as part of the territorialization of public policy, this model involves many different actors, including representatives of civil society and solidarity economy organizations. Many projects developed by these actors focus on distinctive or typical local resources that are subjected to a process of valorization, differentiation, and heritage production. The main issues involved in this approach to heritage and tourism development revolve around the relative importance given to each of the three concepts of resource, terroir, and territory. The result is the development of new forms of territorial construction, operating on different scales, in Southern Morocco. The emergence of territories through new territorial innovation processes, usually initiated by outsiders or by emigrants from the area in question, is based on local leaders or individuals recognizing the potential of local resources and then exploiting them in order to promote local and regional development. The transformations affecting the territorial organization of the hinterlands of the regions’ main tourism centers provide evidence that these areas are opening up to globalization by restructuring their tourism territories as archipelagos.